2016
DOI: 10.1099/ijsem.0.000925
|View full text |Cite
|
Sign up to set email alerts
|

Marinagarivorans algicola gen. nov., sp. nov., isolated from marine algae

Abstract: Two novel agar-degrading, Gram-stain-negative, motile, heterotrophic, facultatively anaerobic and pale yellow-pigmented bacterial strains, designated Z1 and JL1, were isolated from marine algae (Lamouroux) and, respectively. Growth of the isolates was optimal at 28-30 °C, pH 7.0-7.5 and with 2-3 % (w/v) NaCl. Both strains contained Q-8 as the sole respiratory quinone. The major cellular fatty acids in strain Z1 were Cω7, C and summed feature 3 (Cω7 and/or iso-C 2-OH). The predominant polar lipids in strain Z1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…On CA, Arcobacter (Epsilonproteobacteria) and Marinagarivorans (Gammaproteobacteria) were significantly enriched (LDPE, 0%; CA, 21.2 and 20.1%, respectively); on PR, Sphingorhabdus (Alphaproteobacteria; LDPE, 0.1%; PR, 3.4%), Simiduia (Gammaproteobacteria; LDPE, 0%; PR, 25%), Z-35 (Gammaproteobacteria; LDPE, 0%; PR, 2.8%), and Hydrogenophaga (Gammaproteobacteria; LDPE, 0%; PR, 6.2%) were significantly enriched; and on PHB, Simiduia (Gammaproteobacteria; LDPE, 0%; PHB, 7%), Z-35 (Gammaproteobacteria; LDPE, 0%; PHB, 7%); and Acanthopleuribacter (Holophaga; PE, 0.04%; PHB, 2.5%) were significantly enriched (Figure and Supplementary Figure 3 of the Supporting Information). Many of these enriched genera represent bacterial taxa putatively capable of consuming complex carbon substrates, and/or they have also been detected on plastics in previous studies. ,,, Despite the brackish nature of the Baltic Sea, common plastisphere genera were detected. Arcobacter (21.2%), which was one of the most abundant genera on CA after 6 months (Figure and Supplementary Figure 3 of the Supporting Information), is a common plastisphere genus, also detected previously on plastics in sediments. , Arcobacter spp.…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…On CA, Arcobacter (Epsilonproteobacteria) and Marinagarivorans (Gammaproteobacteria) were significantly enriched (LDPE, 0%; CA, 21.2 and 20.1%, respectively); on PR, Sphingorhabdus (Alphaproteobacteria; LDPE, 0.1%; PR, 3.4%), Simiduia (Gammaproteobacteria; LDPE, 0%; PR, 25%), Z-35 (Gammaproteobacteria; LDPE, 0%; PR, 2.8%), and Hydrogenophaga (Gammaproteobacteria; LDPE, 0%; PR, 6.2%) were significantly enriched; and on PHB, Simiduia (Gammaproteobacteria; LDPE, 0%; PHB, 7%), Z-35 (Gammaproteobacteria; LDPE, 0%; PHB, 7%); and Acanthopleuribacter (Holophaga; PE, 0.04%; PHB, 2.5%) were significantly enriched (Figure and Supplementary Figure 3 of the Supporting Information). Many of these enriched genera represent bacterial taxa putatively capable of consuming complex carbon substrates, and/or they have also been detected on plastics in previous studies. ,,, Despite the brackish nature of the Baltic Sea, common plastisphere genera were detected. Arcobacter (21.2%), which was one of the most abundant genera on CA after 6 months (Figure and Supplementary Figure 3 of the Supporting Information), is a common plastisphere genus, also detected previously on plastics in sediments. , Arcobacter spp.…”
Section: Resultsmentioning
confidence: 59%
“…Many of these enriched genera represent bacterial taxa putatively capable of consuming complex carbon substrates, and/or they have also been detected on plastics in previous studies. 43 , 44 , 48 , 49 Despite the brackish nature of the Baltic Sea, common plastisphere genera were detected. Arcobacter (21.2%), which was one of the most abundant genera on CA after 6 months ( Figure 3 and Supplementary Figure 3 of the Supporting Information), is a common plastisphere genus, also detected previously on plastics in sediments.…”
Section: Resultsmentioning
confidence: 99%
“…Identification using 16S rRNA gene sequences ( Weisburg et al., 1991 ) showed that the isolates were classified into the family Cellvibrionaceae within the class γ-Proteobacteria ( Figure 4 C). Strains GE09, Y001, and SGM02 exhibited 97%, 98%, and 99% homology, respectively, to Marinagarivorans algicola Z1 T , a marine degrader of agar and CMC ( Guo et al., 2016 ). The isolates exhibited low homology (92%) to Teredinibacter turnerae T0971 T , which is a marine cellulolytic bacterium isolated from shipworms ( Yang et al., 2009 ).…”
Section: Resultsmentioning
confidence: 99%
“…The ability to degrade complex polysaccharides, such as agarose, chitin and cellulose, is a common feature of this family [2] and has been well studied in the members such as Cellvibrio japonicus [4], Saccharophagus degradans [5] and Teredinibacter turnerae [6]. The genus Marinagarivorans contains one species, Marinagarivorans algicola (with strains Z1 T and JL1), isolated from the surface of red algae [7]. In our previous study, several cellulolytic strains related to the genus Marinagarivorans were isolated [1] from the sea floor at a depth of approximately 200–600 m near Japan, in environments with a relative abundance of chemosynthetic organisms.…”
Section: Introductionmentioning
confidence: 99%
“…Fatty acid contents (%) of strain GE09 T and the type strains of related species Strains: 1, GE09 T ; 2, Marinagarivorans algicola Z1 T[7]; 3, Teredinibacter turnerae T7902 T[7]. -, Not detected; Br, branch; tr, <1 %.…”
mentioning
confidence: 99%